Plant Polysaccharides-Based Multiple-Unit Systems for Oral Drug Delivery - Nayak, Amit Kumar; Hasnain, Md Saquib (SpringerBriefs in Applied Sciences and Technology, 2019)
This book explores the use of various plant polysaccharides for pharmaceutical purposes, including drug delivery. It examines the exploitation of plant polysaccharides' auxiliary functions to enhance drug release, stability, bioavailability and target specificity. Plant-derived materials are at the center of drug-delivery research thanks to their non-toxicity, biodegradability, ready availability, eco-friendliness and low extraction costs. These materials include polysaccharides, a class of naturally occurring polymers consisting of glucose monomers, which serve as storage carbohydrates in cereals, root vegetables, rhizomes, seeds, fruits, etc.